2009
DOI: 10.1007/s00606-008-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Homoploid hybridization in the origin and evolution of wild diploid potato species

Abstract: The potatoes, Solanum L. section Petota Dumortier, are a group of species that possess a very broad range of biological diversity, and a wide geographical distribution in the Americas. These species constitute euploid series with somatic chromosome numbers ranging from 2n = 2x = 24 to 2n = 6x = 72. Although special attention has been given to the origin of polyploid potato species, principally the cultivated forms, that are major food crops, and hybridization has been accepted as an important evolutionary forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 52 publications
1
21
0
2
Order By: Relevance
“…In controlled reciprocal crosses among plants of the same spg and 2x grl accessions used in the present study, some genotypic combinations produced hybrid seeds (34% and 16%, respectively) although many of them exhibited incompatibility reactions (Erazzú and Camadro 2008). These evidences have led Masuelli et al (2009) to the speculation, based on numerous literature reports of over 50 years, that hybridization, specifically interspecific hybridization, can induce genetic and epigenetic changes that can act as creative evolutionary forces in wild potatoes. In this regard, two Argentinean species, chc and spg, are of particular interest, since both of them present a wide range of distribution as well as affinity with a number of species, many of them sympatric.…”
Section: Discussionmentioning
confidence: 98%
“…In controlled reciprocal crosses among plants of the same spg and 2x grl accessions used in the present study, some genotypic combinations produced hybrid seeds (34% and 16%, respectively) although many of them exhibited incompatibility reactions (Erazzú and Camadro 2008). These evidences have led Masuelli et al (2009) to the speculation, based on numerous literature reports of over 50 years, that hybridization, specifically interspecific hybridization, can induce genetic and epigenetic changes that can act as creative evolutionary forces in wild potatoes. In this regard, two Argentinean species, chc and spg, are of particular interest, since both of them present a wide range of distribution as well as affinity with a number of species, many of them sympatric.…”
Section: Discussionmentioning
confidence: 98%
“…Ha et al (2009) have shown that small RNAs serve as a genetic buffer against genomic shock in Arabidopsis interspecific hybrids. Moreover, Masuelli et al (2009) have proposed that homoploid hybridization is the main mechanism involved in the origin and evolution of diploid potato species.…”
Section: Discussionmentioning
confidence: 99%
“…Their breeding system provides for overlapping generations, and hybridization is a frequent phenomenon within and between ploidy levels and populations (Hawkes and D r a f t 10 Hjerting 1969; Masuelli et al 2009) because breeding barriers, if present, can either be incomplete or circumvented (see Camadro et al 2012). Moreover, their natural populations can be composed of plants with more than one ploidy level.…”
Section: Discussionmentioning
confidence: 99%
“…These results contrast with the expected if TS and BS were equivalent in potatoes, and point out to the feasibility of gene flow among sympatric natural populations of different TS. In fact, various authors have reported the occurrence of natural interspecific wild potato hybrids (see Hawkes and Hjerting 1969;Camadro et al 2004Camadro et al , 2012Masuelli et al 2009;Spooner et al 2014), and morphological, genetic and molecular data obtained by Bedonni and Camadro (2009) have revealed the occurrence of gene flow among sympatric populations of four TS.…”
Section: Pollen-pistil Relationships and The Species Concept In Potatoesmentioning
confidence: 99%